Complex structured meat analogues via hybrid extrusion printing by incorporation of oil-containing ionically gelling alginate binders - Laurids Pernice; Luca Dennig; Birgit Hetzer; Eric Gottwald; Ulrike S. van der Schaaf; Nico Leister (Food Hydrocolloids, 2027)

Risk of Pseudomonas spp. in raw milk: Biofilm formation and enhanced peptidase production - Stefanie Gieschler-Lübbehüsen; Jan Kabisch; Birgit Hetzer; Charles M.A.P. Franz; Christina Böhnlein (International Dairy Journal, 2025)

Pressure-assisted isolation of micro- and nanoplastics from food of animal origin with special emphasis on seafood - Julia Süssmann; Elke Walz; Birgit Hetzer; Ralf Greiner; Elke Kerstin Fischer; Sascha Rohn; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2025)
Recent studies have indicated the presence of micro- and nanoplastics in food of animal origin. To address the concerns regarding human dietary plastic uptake, extensive monitoring using validated analytical methods is required. However, a major challenge in analysis lies in the high complexity of preparing food samples rich in macromolecular content (e.g., proteins, complex lipids), such as seafood. Consequently, this study aimed to optimise sample preparation methods for seafood, meat, milk, honey, and eggs, ensuring negligible impact on plastic integrity. Sample matrices were digested using combinations of alkaline, oxidative, and enzymatic approaches, with incubation periods ranging from 6 to 16 h. Particles were rapidly isolated by pressure-assisted filtration, which retained particles in the lower micron range. This method, used for isolating microplastic from food, was compared to the commonly employed vacuum filtration technique. Pressure-assisted filtration improved filtration rates and matrix removal while demonstrating comparable impact on procedural contamination and polymer integrity to vacuum filtration. The feasibility of microplastic analysis was demonstrated using fluorescence imaging. In contrast to microplastics, nanoplastics (< 1 µm) have greater potential for negative biological effects due to their small size, warranting detailed analysis. However, their low particle mass, susceptibility for agglomeration, and the detection limits of conventional spectroscopic techniques pose unique analytical challenges. Addressing these challenges is essential for developing standardised methodologies, including certified food reference material, to enable safety assessments of micro- and nanoplastic in food. Graphical Abstract

Bosea rubneri sp. nov. Isolated from Organically Grown Allium cepa - Dominic A. Stoll; Christina Grimmler; Birgit Hetzer; Alexandra Masoura; Sabine E. Kulling; Melanie Huch (Current Microbiology, 2024)
Strain ZW T0_25 T was isolated from an onion sample ( Allium cepa var. Hytech F1) within a storage trial and proofed to be a novel, aerobic, Gram-stain negative, rod-shaped bacterial strain. Analyses of the 16S rRNA gene sequence and of the whole draft genome sequences, i.e., digital DNA–DNA hybridization (dDDH), Average Nucleotide Identity (ANI) and Average Amino Acid Identity (AAI) showed that this strain represents a new species of the genus Bosea . The genome size of strain ZW T0_25 T is 6.19 Mbp, and the GC content is 66.9%. As whole cell sugars, rhamnose, ribose and glucose were identified. Ubiquinone Q-10 is the major respiratory quinone with 97.8%. Polar lipids in strain ZW T0_25 T are composed of one phosphatidylethanolamine, one phosphatidylglycerol, one aminophospholipid, two aminolipids, one glycolipid and two phospholipids whereas the fatty acid profile predominantly consists of C18:1 w7c (63.3%), C16:1 w7c (19.5%) and C16:0 (7.1%). Phenotypic traits were tested in the wet lab as well as predicted in silico from genome data. Therefore, according to this polyphasic approach, the new name Bosea rubneri sp. nov. with the type strain ZW T0_25 T (= DSM 116094 T = LMG 33093 T ) is proposed.

Similar but not equal – A study on the foam stabilisation mechanism of mechanically whipped cream and aerosol whipping cream - Max Blankart; Birgit Hetzer; Jörg Hinrichs (International Dairy Journal, 2023)

Characterisation of iron oxide-containing pearlescent pigments used as food colourants: nano-labelling required in the EU? - Birgit Hetzer; Volker Gräf; Elke Walz; Ralf Greiner (Food Additives & Contaminants: Part A, 2022)

Characterisation of TiO 2 -containing pearlescent pigments with regard to the European Union labelling obligation of engineered nanomaterials in food - Birgit Hetzer; Volker Gräf; Elke Walz; Ralf Greiner (Food Additives & Contaminants: Part A, 2021)